04 ANALISIS PEMASARAN GABAH UD. NURUL DI KECAMATAN BANTIMURUNG KABUPATEN MAROS - Jurnal Agribis; Sukri Sukri; Musawirah Musawirah; Mohammad Anwar Sadat (Universitas Muslim Maros, 2017)
The research objective is to determine the amount of marketing margins received by marketing agencies involved in grain marketing. And knowing the price received by farmers in marketing grain to the selling price of traders. This research will be conducted at UD. NURUL in Bantimurung District, Maros Regency. The analysis method is marketing margin analysis and selling price analysis. The results of the study are the UD NURUL grain marketing channel in Bantimurung District, Maros Regency is a good marketing channel. This is caused by the marketing channel only slightly increasing marketing costs, namely transportation costs. The marketing margin that occurs for collectors 1, 3 and 5 is Rp 200 while the collecting traders 2 and 4 are Rp 100. The greater marketing margin occurs for collecting traders 1, 3 and 5 due to additional marketing costs incurred in the form of transportation costs.